Seasonal Analysis of the Male Reproductive Tract and Germ Cell Proliferation in Leptodactylus podicipinus (Anura) - Bordin, Rafael O. A. [UNESP]; de Oliveira, Classius [UNESP]; Domeniconi, Raquel F. [UNESP] (Wiley, 2025)
In the reproductive dynamics of anurans, the male gonads have a fundamental relationship with the kidneys. Although reproductive aspects have been widely studied in this group, there are still considerable gaps in understanding the morphology and physiology of the reproductive system of neotropical anurans. Most research has emphasized aspects such as spermatogenesis and reproductive ecology, without information on the structure of the male reproductive tract and the dynamics of spermatogenesis in different species. To better understand the reproductive diversity of anurans, it is essential to comprehend reproductive morphology in a broad sense and simultaneously at different organizational levels. In this context, the present study aimed to characterize the components of the male reproductive tract and assess testicular cell proliferation in Leptodactylus podicipinus throughout its reproductive cycle, using histological, immunohistochemical, and computerized microscopy techniques. The male reproductive tract of this species comprises intratesticular ducts that converge into a longitudinal collecting duct, which gives rise to extratesticular efferent vessels entering the kidneys through lateral ducts. These ducts take the sperm through the glomeruli to the collecting ducts, leading to the Wolffian duct. Differences were observed in the intratesticular ducts of individuals in the reproductive and nonreproductive periods. Additionally, the proliferation of the initial germ cells (spermatogonia and spermatocyte I) exhibited positive PCNA staining, with distinct differences between the two periods analyzed.